Autonomic Computing at Improving Banking Delivery System - Syamsiah, Mahzan@Mohd Zin (2009)
Autonomic computing which promotes self-healing, self-configuring, self-optimizing, and self-protecting hardware and software that behaves in accordance to defined service levels and policies is paramount in banking industry given its complexity of computerized environment. By autonomic computing, it would automate inefficient manual processes taken by system administrators to administer and troubleshoot that would take longer time and efforts to resolve and thus helping to improve in delivering better banking system. However, the challenge to establish autonomic computing is not just from the infrastructure itself but it may also undermine job security of network administrators who have already served the banking industry.